2007
DOI: 10.1098/rspb.2007.0153
|View full text |Cite
|
Sign up to set email alerts
|

Empirical tests of the role of disruptive coloration in reducing detectability

Abstract: Disruptive patterning is a potentially universal camouflage technique that is thought to enhance concealment by rendering the detection of body shapes more difficult. In a recent series of field experiments, artificial moths with markings that extended to the edges of their 'wings' survived at higher rates than moths with the same edge patterns inwardly displaced. While this result seemingly indicates a benefit to obscuring edges, it is possible that the higher density markings of the inwardly displaced patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
129
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(137 citation statements)
references
References 25 publications
(41 reference statements)
7
129
1
Order By: Relevance
“…This study showed that colour blocks that intersected the edge of the 'wing' reduced the rate of attacks on the models compared to otherwise similar controls with only internal patterning, or uniformly coloured. A computer-based experiment using the same sort of targets on pictures of tree bark replicated the results with humans (Fraser et al 2007), suggesting that the perceptual mechanisms being fooled are in common across birds and humans. Most plausible would be continuity of strong edges, suggesting a bounding contour.…”
supporting
confidence: 57%
“…This study showed that colour blocks that intersected the edge of the 'wing' reduced the rate of attacks on the models compared to otherwise similar controls with only internal patterning, or uniformly coloured. A computer-based experiment using the same sort of targets on pictures of tree bark replicated the results with humans (Fraser et al 2007), suggesting that the perceptual mechanisms being fooled are in common across birds and humans. Most plausible would be continuity of strong edges, suggesting a bounding contour.…”
supporting
confidence: 57%
“…2006; Stobbe and Schaefer 2008) and human predators (Fraser et al. 2007). One disruptive coloration pattern that has been demonstrated to have a camouflage effect (e.g., Cuthill et al.…”
Section: Introductionmentioning
confidence: 99%
“…2005, 2006; Merilaita and Lind 2005; Fraser et al. 2007) is the “disruptive marginal pattern,” in which the disruptive markings touch the outline of the prey's body (Cott 1940; Stevens and Merilaita 2009b). Disruptive marginal patterns are effective even when some of the pattern elements do not visually match adjacent parts of the background (Cuthill et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In background matching, the surface of an object is made inconspicuous by having the same coloration as its background (Stevens and Merilaita 2011). In disruptive coloration, distinctive markings, often composed of background-matching colors, are used to create the impression of false boundaries and edges in the object, breaking up its shape and making its outline less easily identifiable (Stevens et al 2006a, 2006b, Fraser et al 2007, Stevens and Merilaita 2011. In the present study, we are concerned primarily with background matching.…”
Section: Introductionmentioning
confidence: 99%